2019
DOI: 10.1111/jssr.12617
|View full text |Cite
|
Sign up to set email alerts
|

Secularity and Irreligion in Cross‐National Context: A Nonlinear Approach

Abstract: As part of the conversation about the characteristics and scope of secularization in contemporary society, the implications of low levels of self‐defined atheism and explicit rejection of religion in nations with low levels of religious beliefs are not yet sufficiently explored. In response, this study uses aggregated data from the World Values Survey, the European Values Study, and Cross‐National Socio‐Economic and Religion Data from the Association of Religion Data Archives to investigate the relationships b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
1
5
0
1
Order By: Relevance
“…Despite the limitations of survey data on religion, they do facilitate comparisons across regions. Even if we take available data at face value and accept that, with nine out of ten Africans claiming that religion is “very important” in their lives and 97.2 per cent claiming to believe in God (Pew Research Center, 2010), “Africa is today the least secular continent” (Kasselstrand, 2019: 631), 8 researchers should be careful about how to interpret African religiosity. In particular, we must resist equating such religiosity with ideal-type adherence to the doctrines promulgated by religious leaders.…”
Section: Challenges For Researching Sub-saharan African Nones: Precon...mentioning
confidence: 99%
“…Despite the limitations of survey data on religion, they do facilitate comparisons across regions. Even if we take available data at face value and accept that, with nine out of ten Africans claiming that religion is “very important” in their lives and 97.2 per cent claiming to believe in God (Pew Research Center, 2010), “Africa is today the least secular continent” (Kasselstrand, 2019: 631), 8 researchers should be careful about how to interpret African religiosity. In particular, we must resist equating such religiosity with ideal-type adherence to the doctrines promulgated by religious leaders.…”
Section: Challenges For Researching Sub-saharan African Nones: Precon...mentioning
confidence: 99%
“…For example, strongly mediatized reports of priests' child abuse, bishops with affairs, and other cleric wrongdoings undermine confidence in the church and lead to distancing from institutional religion (Field, 2014, Keysar, 2014, Bottan and Perez-Truglia, 2015, Turpin et al, 2019, even in a highly religious country like Ireland (Donnelly and Inglis, 2010). The conflict between the churches' public positions and the societies' principles, values, and beliefs (like sexual behavior, family issues, and political orientation) is important for the decay of 'belonging' in terms of confidence in the church and the trust in religious leaders (Hoffmann, 1998, Nicolet and Tresch, 2009, Lüchau and Andersen, 2012, Hoffmann, 2013, Field, 2014, Kasselstrand et al, 2017, Kasselstrand, 2019, because of the interplay between ' cultural religion' and cultural values in Scandinavia (Kasselstrand, 2015;Demerath, 2020).…”
Section: Religion In Scandinavia: Tradition Vs Secularizationmentioning
confidence: 99%
“…Not surprisingly, there is a significant association between religious affiliation and belief in God (see Sherkat (2008), or Urstad (2017) for a recent study on Norway). In a recent cross-national study involving 77 countries, Kasselstrand (2019) found a nonlinear relationship between secularity, measured by the percentage of the population in a country that does not believe in God, and irreligion, measured by the percentages of self-defined atheists and individuals with no confidence at all in religions organizations in a country. However, this study has two limitations.…”
Section: Religion In Scandinavia: Tradition Vs Secularizationmentioning
confidence: 99%
“…Forskning i irreligion (non-religion, unbelief, ateisme) har de seneste tyve år for alvor vundet indpas. I den vestlige del af verden er antallet af irreligiøse individer støt voksende (Kasselstrand 2019, Jensen 2020, Lanman et al 2019, og i et kendt estimat vurderede Phil Zuckerman, at der var mellem 500-700 millioner ateister på globalt plan (Zuckerman 2007, 61), om end flere forskere peger på, at dette tal kan vaere endnu højere, fordi det i mange lande kan vaere problematisk at definere sig som irreligiøs (Gervais og Najle 2018). Antropologer, sociologer, psykologer og historikere undersøger irreligiøsitet ved hjaelp af et vaeld af metoder.…”
Section: Indledningunclassified